Le monument naturel dans le mythe de l’Ouest chez Washington Irving, Mark Twain et Walt Whitman - Delphine Louis-Dimitrov (Transatlantica)
This article deals with the image of the natural monument and considers its function in 19th-century representations of the West, especially in three travel narratives—A Tour on the Prairies by Washington Irving, Roughing It by Mark Twain and Specimen Days by Walt Whitman. An emblem of the old European nations, the monument is paradoxically omnipresent in the representations of the Western wilderness and appears as a structuring paradigm. The purpose of this reflexion is to analyse jointly the aesthetic and political implications of its transposition onto the American soil. Indeed, this motive on which the construction of the Western landscape is based also appears as the embodiment of American democracy while defining a writing principle.